2022
DOI: 10.1155/2022/3961647
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Sustainable Development Research of Green Smart Park in High‐End Manufacturing Based on Internet of Things

Abstract: During the transition from industrial production to intelligent, there are still a large number of manufacturing industries in the traditional production mode. The problems of slow information transmission, difficult integrated production management, and complicated process parameter control have led to disconnect decision-making from actual production. In addition, the current manufacturing industry is more of a traditional management method, and the upgrade and iteration speed are slow, and it is not combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…With the rapid growth of information and communication technology, the demand for communication and basic data of businesses related to intelligent power distribution stations, accurate load prediction and dispatch, energy management and demand-side response is gradually increasing. An intelligent sensing system that enables complete, high-performance, steady-state real-time data acquisition and monitoring is the basis for subsequent data analysis, optimization and control, as well as a prerequisite for promoting high-quality development of the park [2,3]. It is said that the intelligent sensing system is the digital basis for the entire zero-carbon park operation.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of information and communication technology, the demand for communication and basic data of businesses related to intelligent power distribution stations, accurate load prediction and dispatch, energy management and demand-side response is gradually increasing. An intelligent sensing system that enables complete, high-performance, steady-state real-time data acquisition and monitoring is the basis for subsequent data analysis, optimization and control, as well as a prerequisite for promoting high-quality development of the park [2,3]. It is said that the intelligent sensing system is the digital basis for the entire zero-carbon park operation.…”
Section: Introductionmentioning
confidence: 99%
“…Bu noktada nesnelerin interneti (IoT) izleme teknolojisi, yeşil akıllı parkların geliştirilmesi için ekolojik ve ekonomik hedefleri hizalayarak üretimi iyileştirebilir. Bu iyileşme yeşil ve dijital dönüşümün bir ifadesidir ve geleneksel ayakkabı endüstrisi açısından değerlendirildiğinde sürdürülebilir kalkınma için inşa edilmesi beklenen yeşil ve akıllı bir parka yönelik teorik bir referans sağlar (Deng, 2022).…”
unclassified
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%